(untitled) (Indian Journal of Animal Production and Management, 2025)
Small ruminants plays an important role in rainfed agriculture. Rearing of ram lambs for fattening is a common practice in scarce rainfall zone of Andhra Pradesh. The usual method of rearing is extensive system and provision of night shelter with mud floor. Elevated floor system has many advantages to eliminate the existing problem of ammonia accumulation in the shed and suitable for intensive feeding which also reduces the cost on labour. Rearing of poultry and ram lambs under one shelter with a concept of two-layer livestock system was developed at KVK, Yagantipalle. The present study was conducted to assess the growth performance of ram lambs and Aseel poultry under different systems. Higher body weight gain of Ram lambs and poultry was observed under two-layer system compared to traditional system.